ABCG2 is associated with HER-2 Expression, lymph node metastasis and clinical stage in breast invasive ductal carcinoma - Gao Peng; Wang Yan; Liu Zhiyan; Xia Shujun; Su Peng; Xiang Lei; Zhou Genyin (BMC, 2011)
Abstract Background ABCG2 is an ABC transporter. It has been demonstrated that endogenous ABCG2 expression in certain cancers is a possible reflection of the differentiated phenotype of the cell of origin and likely contributes to intrinsic drug resistance. But little is known about the contribution of ABCG2 to the drug resistance and the clinicopathological characteristics in breast cancer. In the present study, we investigated the expression of ABCG2 and the correlations between ABCG2 expression and patients' clinicopathological and biological characteristics. Methods Immunohistochemistry was employed on the tissue microarray paraffin sections of surgically removed samples from 196 breast cancer patients with clinicopathological data. Results The results showed that ABCG2 was expressed in different intensities and distributions in the tumor cells of the breast invasive ductal carcinoma. A positive stain for ABCG2 was defined as a brown stain observed in the cytoplasm and cytomembrane. A statistically significant correlation was demonstrated between ABCG2 expression and HER-2 expression (p = 0.001), lymph node metastasis (p = 0.049), and clinical stage (p = 0.015) respectively. Conclusion ABCG2 correlated with Her-2 expression, lymph node metastasis and clinical stage in breast invasive ductal carcinoma. It could be a novel potential bio-marker which can predict biological behavior, clinical progression, prognosis and chemotherapy effectiveness.